Maximizing the Treatment Benefit of tDCS in Neurodegenerative Anomia - Roncero, Carlos; Service, Erik; De Caro, Marco; Popov, Aleksandar; Thiel, Alexander; Probst, Stephan; Chertkow, Howard (Frontiers in Neuroscience, 2019)
We evaluated whether transcranial direct current stimulation (tDCS) in two different montages could improve picture naming abilities in participants with anomic Alzheimer Disease or Frontotemporal dementia. Methods: Utilizing a double-blind cross-over design, twelve participants were trained on picture naming over a series of 10 sessions with 30 minutes of anodal (2 mA) tDCS stimulation to either the left inferior parietotemporal region (P3), the left dorsolateral prefrontal cortex (F3), or sham stimulation. We evaluated performance on a trained picture naming list, an equivalent novel untrained list, and additional neuropsychological tasks. Results: For trained item picture naming, significantly larger improvement was seen for real stimulation vs. sham stimulation for both the DLPFC and left inferior parieto-temporal stimulation montages at the end of the stimulation sessions. The parieto-temporal montage remained superior to sham two weeks poststimulation. Significant improvement vs. sham was also seen for novel “untrained” item picture naming two weeks post-stimulation when the parieto-temporal montage was given, whereas no change was observed when the DLPFC montage was given. Finally, comparing groups when they received the parieto-temporal montage, participants with semantic variant Primary Progressive Aphasia showed the least improvement for untrained items after their sessions. Scores on the additional neuropsychological tasks were unchanged. Conclusions: tDCS stimulation has promise as a treatment for individuals with anomia arising from neurodegenerative disease, but its effectiveness can vary depending on the training given, the montage location used, as well as a participants’ diagnosis.